RESEARCH AND QUALITY ASSURANCE OF THE LARGE VALVES MANUFACTURE FOR TRUNK PIPELINES - Gabdyssalyk, Riza; Sherov, Karibek; Tussupova, Sayagul; Zharkevich, Olga; Mirgorodskiy, Sergey; Izotova, Aigerim; Taskarina, Aizhan; Mazdubay, Assylkhan; Sagitov, Almat (Journal of Applied Engineering Science, 2020)
This article deals with analysis of the production state of pipeline valves in the Republic of Kazakhstan (RK). As a result of the study, it was found that to ensure high reliability and complete environmental safety of the communications system of pipeline transport, it is necessary to improve the quality of manufacturing pipeline valves and other elements of the pipeline transport system by using new promising developments in the field of mechanical processing, assembly, welding, etc. The relevance of the study is the issues of the large valves manufacturing for pipelines. The design and classification of pipelines, pipe fittings, in particular, valves, have been investigated. It has been established that the most difficult and time consuming to manufacture among pipeline valves is the design of gate valves. The technology of manufacturing large-sized gate valves in the conditions of the Ust-Kamenogorsk reinforcement plant has been investigated and the issues of quality and accuracy assurance in the manufacture of a box assembly have been identified. The results of experimental studies of the milling process of a tapered surface have shown the possibility of using a friction cone cutter for machining holes with curvilinear surfaces of a semi-hull of a large-sized sliding gate valve.